Alkylammonium Ions as Carriers of Metal Oxidants - Sahu, Sandhyamayee; R. Sahoo, Prangya; K. Mishra, Bijay (Current Organic Chemistry, 2017)
Salts of various oniums such as ammonium, phosphonium, tellurium, arsonium, bismuthenium have been used as phase transfer catalyst in many oxidation reactions. These ions are also in use as carriers of anionic oxidants such as permanganate, chromate, dichromate, etc. Among these oniums, alkylammonium ions have been extensively studied. Alkylammonium ions are charged molecules, susceptible for acquiring hydrophobic characteristics through carboneous groups present in the molecule. Variation of these groups can tune the hydrophobicity of the oniums; thereby these molecules can acquire amphipathic characteristics. In different solutions, these ions aggregate to form different organized assemblies providing different localization sites for the oxidants. These oxidants exist as tight ion pairs with the oniums and follow different reaction mechanism during the oxidation reactions of various irganic substrates. The X-ray crystal strudies as well as reaction kinetics support the existence of tight ion pairs in both solid state and in solutions. The variation of substituent in the substrate, and the polarity of the solvent are found to have significant effect on the oxidation kinetics and reaction mechanism. Herein, we focus the review on the alkyl ammonium ions as carriers of oxidants and described the kinetics and reaction mechanism of the oxidation processes.
Keywords: phase transfer catalysis